O discurso de vereadores de um município do Estado de Minas Gerais: aproximações com a representação teatral e distanciamento da dialogicidade - Juliana Cristina Teixeira; Priscila Gomes de Araújo; Mariana Pereira Chaves Pimentel; Flávia Luciana Naves Mafra (Ciências Sociais Unisinos)
This study performs a critical analysis of the posture of aldermen of a town in the state of Minas Gerais through a dialogue between different theoretical perspectives. It demonstrates the proximity of political representation to theatrical performance, using a critical epistemological posture. It uses the notion of political representation as staging, or as political theater or social theater, in which elected politicians end up assuming the role of decision makers, instead of the citizens, and the latter, in turn, end up assuming the role of spectators. The purpose of the performance by the aldermen is to direct and regulate the impression that the citizens might make of them, through the control of expression. These ideas are supported by Rousseau (1978), who suggests a parallel between parliamentary representation and the modern theatrical performance, adopting a critical stance toward both. The study adopted a qualitative methodology, using semi-structured interviews. The analysis of the aldermen¿s discourse shows that, in fact, their behavior evokes elements of a theatrical performance, which become more intense when they discuss the television broadcasting of the town council¿s sessions. Thus, it is considered that such behavior is distant from a public representation that ensures a dialogical decision-making process, i.e., that is close to the will of the represented ones.